Perancangan Sistem Penjualan untuk mempermudah Manajemen dan Laporan Penjualan Cat Menggunakan Website - Febryantahanuji Febryantahanuji; Hadi Yusuf; Budi Hartono; Arsito Ari Kuncoro; Zaenal Mustofa (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2024)
This research aims to identify the issues faced by one of the paint distributors in managing their sales information system. The study notes that despite the store's successful sales activities, the utilization of the sales information system remains limited, with the store preferring to manage products without online information handling applications. Based on observations, some weaknesses of the current system include lack of stock data accuracy, hindrances in providing real-time stock information, and limitations in tracking stock changes. The author suggests providing training to users of the web-based sales information system and establishing clear task allocation, as well as system improvements to address existing weaknesses. These suggestions are expected to enhance efficiency and effectiveness in sales management and meet the needs of both administrators and buyers.